We have "f(T)=-T^3+2I"
"T\\begin{pmatrix}\nx_1\\\\\nx_2\\\\\nx_3\n\\end{pmatrix}=\\begin{pmatrix}\n1&0&0\\\\\n0&0&1\\\\\n0&-2&-1\n\\end{pmatrix}\\begin{pmatrix}\nx_1\\\\\nx_2\\\\\nx_3\n\\end{pmatrix}"
Then "f(T)\\begin{pmatrix}\nx_1\\\\\nx_2\\\\\nx_3\n\\end{pmatrix}=(-T^3+2I)\\begin{pmatrix}\nx_1\\\\\nx_2\\\\\nx_3\n\\end{pmatrix}="
"=\\left(-\\begin{pmatrix}\n1&0&0\\\\\n0&0&1\\\\\n0&-2&-1\n\\end{pmatrix}^3+\\begin{pmatrix}\n2&0&0\\\\\n0&2&0\\\\\n0&0&2\n\\end{pmatrix}\\right)\\begin{pmatrix}\nx_1\\\\\nx_2\\\\\nx_3\n\\end{pmatrix}"
"\\begin{pmatrix}\n1&0&0\\\\\n0&0&1\\\\\n0&-2&-1\n\\end{pmatrix}^2=\\begin{pmatrix}\n1&0&0\\\\\n0&0&1\\\\\n0&-2&-1\n\\end{pmatrix}\\begin{pmatrix}\n1&0&0\\\\\n0&0&1\\\\\n0&-2&-1\n\\end{pmatrix}="
"=\\begin{pmatrix}\n1&0&0\\\\\n0&-2&-1\\\\\n0&2&-1\n\\end{pmatrix}"
"\\begin{pmatrix}\n1&0&0\\\\\n0&0&1\\\\\n0&-2&-1\n\\end{pmatrix}^3=\\begin{pmatrix}\n1&0&0\\\\\n0&0&1\\\\\n0&-2&-1\n\\end{pmatrix}^2\\begin{pmatrix}\n1&0&0\\\\\n0&0&1\\\\\n0&-2&-1\n\\end{pmatrix}="
"=\\begin{pmatrix}\n1&0&0\\\\\n0&-2&-1\\\\\n0&2&-1\n\\end{pmatrix}\\begin{pmatrix}\n1&0&0\\\\\n0&0&1\\\\\n0&-2&-1\n\\end{pmatrix}=\\begin{pmatrix}\n1&0&0\\\\\n0&2&-1\\\\\n0&2&3\n\\end{pmatrix}"
"-\\begin{pmatrix}\n1&0&0\\\\\n0&0&1\\\\\n0&-2&-1\n\\end{pmatrix}^3+\\begin{pmatrix}\n2&0&0\\\\\n0&2&0\\\\\n0&0&2\n\\end{pmatrix}=-\\begin{pmatrix}\n1&0&0\\\\\n0&2&-1\\\\\n0&2&3\n\\end{pmatrix}+\\begin{pmatrix}\n2&0&0\\\\\n0&2&0\\\\\n0&0&2\n\\end{pmatrix}=\\begin{pmatrix}\n1&0&0\\\\\n0&0&1\\\\\n0&-2&-1\n\\end{pmatrix}"
We obtain "f(T)\\begin{pmatrix}\nx_1\\\\\nx_2\\\\\nx_3\n\\end{pmatrix}=\\begin{pmatrix}\n1&0&0\\\\\n0&0&1\\\\\n0&-2&-1\n\\end{pmatrix}\\begin{pmatrix}\nx_1\\\\\nx_2\\\\\nx_3\n\\end{pmatrix}=T\\begin{pmatrix}\nx_1\\\\\nx_2\\\\\nx_3\n\\end{pmatrix}" , that is "f(T)=T"
Answer: "f(T)=T"
Comments
Leave a comment